Conductive adhesive as well as preparation method and application thereof

By using a combination of acrylic resin and surface modified silver powder in conductive adhesives, the problem of lightning-type cracks in the chip packaging process is solved, and higher bonding strength and stronger reliability are achieved.

CN119799265APending Publication Date: 2025-04-11XIAMEN WELDTONE TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510052198.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-14
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

Conductive adhesives are prone to lightning cracks during chip packaging, resulting in damage to the packaging structure, reduced bonding strength, reliability failure and electrical performance affected.

Method used

The combination of acrylic resin and surface-modified silver powder is used to prepare acrylic surface-modified silver powder as a conductive filler through Steglich esterification, which improves the compatibility and dispersion of silver powder and resin, avoids the existence of bubbles, and thus reduces the occurrence of lightning-type cracks.

Benefits of technology

It effectively avoids lightning-type cracks caused by conductive adhesives after curing, improves the bonding strength at the metal interface, and enhances the reliability and electrical performance of the package.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119799265A_ABST
    Figure CN119799265A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of conductive adhesives, and particularly relates to a conductive adhesive capable of effectively reducing generation of bubbles in the curing process and a preparation method and application thereof. The conductive adhesive contains acrylic resin, silver powder and an initiator, the silver powder at least contains more than 10 wt% of acrylic surface modified silver powder, and the mass ratio of the acrylic resin to the silver powder is 100: (100-1000). The conductive adhesive provided by the invention is not easy to generate lightning cracks in a chip packaging process, so that higher bonding strength can be obtained at a metal interface, and the problem of reliability failure of the conductive adhesive after curing is avoided.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of conductive adhesives and relates to a conductive adhesive and a preparation method and application thereof. Background Art

[0002] Conductive adhesives are often used in the chip packaging process. Lightning cracks in adhesives refer to fast and obvious cracks that occur during the curing or use of adhesives. The generation of lightning cracks has many adverse effects. First, in the chip packaging process, adhesives play an important role in fixing, protecting and providing electrical connections. If lightning cracks appear in the adhesive, the integrity of the packaging structure will be directly destroyed, and the chips, leads and other components inside the package will lose protection and be easily affected by the external environment (such as moisture, dust, vibration, etc.). Second, the presence of lightning cracks will weaken the bonding strength of the adhesive, thereby reducing the reliability of the package. During long-term use, due to the effects of vibration, temperature changes and other factors, the cracks may gradually expand, which may eventually cause the package to fail, the chip to fail to work properly, and even cause the entire electronic device to fail. Third, cracks in the adhesive may also affect the electrical properties of the package. For example, cracks may cause poor electrical connections inside the package, open circuits or short circuits. Fourth, cracks may also cause electromagnetic interference, affecting the normal operation of electronic equipment. In addition, since cracks may cause the package to fail, it is necessary to replace the package with a new one or perform repair operations, which will increase the packaging cost and time cost, and have an adverse impact on production efficiency and economic benefits.

[0003] Since conductive adhesives need to add flaky or granular conductive fillers to the adhesive, they are more likely to produce lightning cracks than other adhesives. In view of this, how to avoid the generation of lightning cracks in conductive adhesives has become a technical problem that needs to be solved urgently in the chip packaging process. Summary of the invention

[0004] The purpose of the present invention is to overcome the defect that the existing conductive adhesive is prone to generate lightning cracks during the chip packaging process, and to provide a conductive adhesive that is not prone to generate lightning cracks during the chip packaging process.

[0005] The second object of the present invention is to provide a method for preparing the conductive adhesive.

[0006] The third object of the present invention is to provide application of the above conductive adhesive in electronic product assembly.

[0007] Specifically, the conductive adhesive provided by the present invention contains acrylic resin, silver powder and an initiator, the silver powder contains at least 10wt% of acrylic surface modified silver powder, and the mass ratio of the acrylic resin to the silver powder is 100:(100-1000).

[0008] The preparation method of the conductive adhesive provided by the invention comprises the steps of uniformly mixing acrylic resin, silver powder and an initiator.

[0009] The key to the present invention is to modify at least part of the silver powder surface with an acrylic compound, and use the obtained acrylic surface modified silver powder as a conductive filler for an acrylic conductive adhesive, thereby effectively avoiding the generation of lightning cracks in the acrylic conductive adhesive after curing, thereby obtaining a higher bonding strength at the metal interface, and avoiding the problem of reliability failure of the conductive adhesive after curing. The reason why the above method can effectively avoid the generation of lightning cracks is speculated to be that: modifying the silver powder surface with an acrylic compound can, on the one hand, increase the compatibility of the silver powder with the conductive adhesive resin, so that the silver powder is well dispersed in the conductive adhesive; on the other hand, the presence of bubbles in the adhesive system is an important cause of lightning cracks. Modifying the silver powder surface with an acrylic compound can make it bonded tightly together with the matrix resin when it is cured, and the bubbles between the silver powder and the matrix resin can be effectively squeezed out, thereby avoiding the generation of lightning cracks due to the presence of bubbles. BRIEF DESCRIPTION OF THE DRAWINGS

[0010] Figure 1 A schematic diagram of a method for preparing acrylic acid surface-modified silver powder provided by the present invention;

[0011] Figure 2 The bubble test results of the conductive adhesives obtained in the examples and comparative examples are shown in FIG. DETAILED DESCRIPTION

[0012] The conductive adhesive provided by the present invention contains acrylic resin, silver powder and initiator. The mass ratio of the acrylic resin to the silver powder is preferably 100:(100-1000), more preferably 100:(200-400), such as 100:200, 100:220, 100:250, 100:280, 100:300, 100:320, 100:350, 100:380, 100:400 or any value therebetween. The mass ratio of the acrylic resin to the initiator is preferably 100:(1-10), more preferably 100:(2-6), such as 100:2, 100:3, 100:4, 100:5, 100:6 or any value therebetween.

[0013] In the above conductive adhesive, the silver powder contains at least acrylic surface modified silver powder, specifically, all of which can be acrylic surface modified silver powder, or a mixture of acrylic surface modified silver powder and unmodified silver powder. Wherein, based on the total weight of the silver powder, the content of the acrylic surface modified silver powder is more than 10wt%, such as 10wt%, 15wt%, 20wt%, 25wt%, 30wt%, 35wt%, 40wt%, 45wt%, 50wt%, 55wt%, 60wt%, 65wt%, 70wt%, 75wt%, 80wt%, 85wt%, 90wt%, 95wt%, 100wt% or any value therebetween. Particularly preferably, the silver powder contains 5-50wt% of acrylic surface modified silver powder and 50-95wt% of unmodified silver powder, in which case the surface modified silver powder is sufficient to wrap up the unmodified silver powder, thereby better avoiding the generation of cracks. Specifically, based on the total weight of the silver powder, the content of the acrylic surface-modified silver powder is preferably 5 to 50 wt%, such as 5 wt%, 10 wt%, 15 wt%, 20 wt%, 25 wt%, 30 wt%, 35 wt%, 40 wt%, 45 wt%, 50 wt% or any value therebetween; the content of the unmodified silver powder is preferably 50 to 95 wt%, such as 50 wt%, 55 wt%, 60 wt%, 65 wt%, 70 wt%, 75 wt%, 80 wt%, 85 wt%, 90 wt%, 95 wt% or any value therebetween.

[0014] In the above conductive adhesive, the acrylic surface modified silver powder is prepared according to the following method: S1. The surface of the silver powder to be modified is hydroxylated to obtain hydroxylated silver powder; S2. The hydroxylated silver powder and an acrylic compound are subjected to a Steglich esterification reaction to obtain acrylic surface modified silver powder. Taking acrylic acid as an example, the specific preparation process of the acrylic surface modified silver powder is as follows: Figure 1 shown.

[0015] In the preparation process of the above-mentioned acrylic acid surface modified silver powder, in step S1, the method of hydroxylating the surface of the silver powder is not particularly limited, and can be carried out according to various existing methods, as long as the surface of the silver powder can be bonded with hydroxyl groups. In a preferred embodiment, the step of hydroxylating the surface of the silver powder includes: placing the silver powder to be modified in a hydrogen peroxide solution at 40°C to 60°C for 10min to 60min, then washing the obtained reaction product with tetrahydrofuran and deionized water in turn, and then drying the obtained washed product to obtain hydroxylated silver powder. Wherein, the concentration of the hydrogen peroxide solution is preferably 60% to 80%, such as 60%, 62%, 65%, 68%, 70%, 72%, 75%, 78%, 80% or any value therebetween. The dosage ratio of the silver powder to the hydrogen peroxide solution is preferably 1g:(30-100)mL, such as 1g:30mL, 1g:35mL, 1g:40mL, 1g:45mL, 1g:50mL, 1g:55mL, 1g:60mL, 1g:65mL, 1g:70mL, 1g:75mL, 1g:80mL, 1g:85mL, 1g:90mL, 1g:95mL, 1g:100mL or any value therebetween. The reaction temperature can be, for example, 40°C, 42°C, 45°C, 48°C, 50°C, 52°C, 55°C, 58°C, 60°C or any value therebetween. The reaction time can be, for example, 10min, 20min, 30min, 40min, 50min, 60min or any value therebetween. The drying conditions may, for example, include a temperature of 50°C to 70°C, such as 50°C, 52°C, 55°C, 58°C, 60°C, 62°C, 65°C, 68°C, 70°C or any value therebetween; and a time of 10h to 48h, such as 10h, 15h, 20h, 24h, 28h, 32h, 36h, 40h, 42h, 48h or any value therebetween.

[0016] In the preparation process of the acrylic surface modified silver powder, in step S2, the usage ratio of the acrylic compound to the hydroxylated silver powder is preferably (0.5-2) mol:1 g. Based on the usage of hydroxylated silver powder as 1 g, the usage of the acrylic compound is preferably 0.5 mol, 0.8 mol, 1 mol, 1.2 mol, 1.5 mol, 1.8 mol, 2 mol or any value therebetween.

[0017] In the preparation process of the above-mentioned acrylic acid surface-modified silver powder, in step S2, the acrylic compound can be various existing compounds with unsaturated double bonds and carboxyl groups, such as at least one of acrylic acid, methacrylic acid and 2-ethylacrylic acid.

[0018] In the preparation process of the above-mentioned acrylic surface modified silver powder, in step S2, the Steglich esterification reaction is carried out in the presence of dimethylaminopyridine and dicyclohexylcarbodiimide. Wherein, the dimethylaminopyridine (DMAP) is used as a catalyst for the Steglich esterification reaction, and the dicyclohexylcarbodiimide (DCC) is used as a shrinking agent for the Steglich esterification reaction. The Steglich esterification reaction is carried out in the presence of these two, which can accelerate the reaction rate and improve the yield. Wherein, the amount ratio of the dimethylaminopyridine to the hydroxylated silver powder is preferably (0.08~0.12) mol: 1g. The amount ratio of the dicyclohexylcarbodiimide to the hydroxylated silver powder is preferably (0.8~1.2) mol: 1g. Specifically, based on the amount of hydroxylated silver powder as 1 g, the amount of the dimethylaminopyridine is preferably 0.08 mol, 0.085 mol, 0.09 mol, 0.095 mol, 0.1 mol, 0.105 mol, 0.11 mol, 0.115 mol, 0.12 mol or any value therebetween; the amount of the dicyclohexylcarbodiimide is preferably 0.8 mol, 0.82 mol, 0.85 mol, 0.88 mol, 0.9 mol, 0.92 mol, 0.95 mol, 0.98 mol, 1 mol, 1.02 mol, 1.05 mol, 1.08 mol, 1.1 mol, 1.12 mol, 1.15 mol, 1.18 mol, 1.2 mol or any value therebetween.

[0019] In the preparation process of the above-mentioned acrylic acid surface modified silver powder, in step S2, the conditions of the Steglich esterification reaction preferably include a temperature of 0°C to 30°C, such as 0°C, 2°C, 5°C, 8°C, 10°C, 12°C, 15°C, 18°C, 20°C, 22°C, 25°C, 28°C, 30°C or any value therebetween; and a time of 10h to 48h, such as 10h, 12h, 16h, 18h, 20h, 24h, 28h, 30h, 32h, 26h, 40h, 42h, 44h, 48h or any value therebetween.

[0020] In the above-mentioned conductive adhesive, the type of the acrylic resin is not particularly limited, and preferably contains acrylate monomers and polyurethane acrylate oligomers. In a preferred embodiment, based on the total weight of the acrylic resin, the proportion of acrylate monomers in the acrylic resin is 75-95wt%, and the proportion of polyurethane acrylate oligomers is 5-25wt%. The use of acrylate monomers and polyurethane acrylate oligomers in this preferred ratio as acrylic resin can more effectively reduce the modulus of the glue. Specifically, the proportion of the acrylate monomer can be 75wt%, 78wt%, 80wt%, 82wt%, 85wt%, 88wt%, 90wt%, 92wt%, 95wt% or any value therebetween. The proportion of the polyurethane acrylate oligomer can be 5wt%, 8wt%, 10wt%, 12wt%, 15wt%, 18wt%, 20wt%, 22wt%, 25wt% or any value therebetween. The acrylate monomers may include at least one of acrylic acid, methacrylic acid, methyl acrylate, methyl methacrylate, ethyl acrylate, ethyl methacrylate and isobornyl methacrylate, and isobornyl methacrylate is particularly preferred. The inventors of the present invention have found that the conductive adhesive obtained by compounding isobornyl methacrylate and polyurethane acrylate oligomer in a ratio of (75-95wt%): (5-25wt%) as acrylic resin has better adhesion.

[0021] The present invention has no particular limitation on the type of initiator, and the initiator may be selected from at least one of an azo initiator, a peroxide initiator, and a redox initiator. Specific examples of the azo initiator include, but are not limited to, at least one of dimethyl azobisisobutyrate, azobisisobutyramidine hydrochloride, azodicarbonamide, azobisisopropylimidazoline hydrochloride, azoisobutylcyanoformamide, azobiscyclohexylcarbonitrile, azobiscyanovaleric acid, azobisisopropylimidazoline, azobisisobutyronitrile, azobisisovaleronitrile, and azobisisoheptylonitrile. Specific examples of the peroxide initiator include, but are not limited to, at least one of hydrogen peroxide, ammonium persulfate, sodium persulfate, potassium persulfate, benzoyl peroxide, diisopropyl peroxide, and tert-butyl benzoyl peroxide. Specific examples of the redox initiator include, but are not limited to, at least one of sulfate-sulfite, persulfate-thiourea, persulfate-organic salt, and ammonium persulfate-fatty amine. Wherein, the sulfate-sulfite can be selected from at least one of sodium sulfate-sodium sulfite, potassium sulfate-potassium sulfite and ammonium sulfate-ammonium sulfite. The persulfate-thiourea can be selected from at least one of sodium persulfate-thiourea, potassium persulfate-thiourea and ammonium persulfate-thiourea. The persulfate-organic salt can be selected from at least one of sodium persulfate-potassium acetate, potassium persulfate-potassium acetate and ammonium persulfate-ammonium acetate. The ammonium persulfate-fatty amine can be ammonium persulfate-N,N-tetramethylethylenediamine and / or ammonium persulfate-diethylamine. In addition, the amount of the initiator preferably accounts for 0.5 to 5wt% of the mass of the acrylic resin, such as 0.5wt%, 0.8wt%, 1wt%, 1.5wt%, 2wt%, 2.5wt%, 3wt%, 3.5wt%, 4wt%, 4.5wt%, 5wt% or any value therebetween.

[0022] The preparation method of the conductive adhesive provided by the present invention comprises mixing acrylic resin, silver powder and initiator uniformly. The mixing method is not particularly limited, and all materials can be added and mixed uniformly at the same time, or two materials can be randomly selected and mixed first, and then other materials are added and mixed uniformly.

[0023] In addition, the present invention also provides application of the conductive adhesive in electronic product assembly.

[0024] The present invention will be described in detail below through examples.

[0025] In the following examples and comparative examples, polyurethane acrylate oligomer was purchased from Changxing Materials with a brand name of 6113; silver powder was purchased from MERALOR with a brand name of SA-54327 and a particle size D90 of 5.4 μm.

[0026] Preparation Example 1

[0027] S1. Place 1 g of silver powder in 50 mL of 70% hydrogen peroxide solution, heat the mixture at 50°C for 30 min, wash the resulting reaction product with tetrahydrofuran and deionized water in sequence to fully rinse the surface of the silver powder, then place the silver powder in a vacuum oven at 60°C overnight and dry it for later use to obtain hydroxylated silver powder.

[0028] S2. Dissolve 1 mol of acrylic acid and 0.1 mol of dimethylaminopyridine (DMAP) in 40 mL of dichloromethane to obtain an acrylic acid solution, place 1 g of hydroxylated silver powder and the acrylic acid solution in a reaction bottle, and stir for 10 min under a nitrogen atmosphere and in an ice bath to obtain liquid A. Dissolve 1 mol of dicyclohexylcarbodiimide (DCC) in 15 mL of dichloromethane, and drop the obtained liquid B into the above-mentioned liquid A in the ice bath within 15 min. After the dropwise addition is completed, react at 25°C ± 2°C for 12 h. After the reaction is completed, filter the reaction mixture, then wash with dichloromethane, tetrahydrofuran and petroleum ether in turn, and then place it in a nitrogen oven overnight to evacuate, and obtain acrylic acid surface-modified silver powder, which is recorded as A1.

[0029] Preparation Example 2

[0030] S1. Place 1 g of silver powder in 50 mL of 70% hydrogen peroxide solution, heat the mixture at 40°C for 60 min, wash the resulting reaction product with tetrahydrofuran and deionized water in sequence to fully rinse the surface of the silver powder, then place the silver powder in a vacuum oven at 60°C overnight and dry it for later use to obtain hydroxylated silver powder.

[0031] S2. Dissolve 1 mol of acrylic acid and 0.1 mol of dimethylaminopyridine (DMAP) in 40 mL of dichloromethane to obtain an acrylic acid solution, place 0.5 g of hydroxylated silver powder and the acrylic acid solution in a reaction bottle, stir for 10 min under a nitrogen atmosphere and in an ice bath to obtain liquid A. Dissolve 1 mol of dicyclohexylcarbodiimide (DCC) in 15 mL of dichloromethane, drop the obtained liquid B into the above-mentioned liquid A in the ice bath within 15 min, and react at 5°C ± 2°C for 48 h after the dropwise addition. After the reaction is completed, filter the reaction mixture, then wash with dichloromethane, tetrahydrofuran and petroleum ether in turn, and then place it in a nitrogen oven overnight to evacuate, and obtain acrylic acid surface-modified silver powder, which is recorded as A2.

[0032] Preparation Example 3

[0033] S1. Place 1 g of silver powder in 50 mL of 70% hydrogen peroxide solution, heat the mixture at 60°C for 10 min, wash the resulting reaction product with tetrahydrofuran and deionized water in sequence to fully rinse the surface of the silver powder, then place the silver powder in a vacuum oven at 60°C overnight and dry it for later use to obtain hydroxylated silver powder.

[0034] S2. Dissolve 1 mol of acrylic acid and 0.1 mol of dimethylaminopyridine (DMAP) in 40 mL of dichloromethane to obtain an acrylic acid solution, place 1.5 g of hydroxylated silver powder and the acrylic acid solution in a reaction bottle, stir for 10 min under a nitrogen atmosphere and in an ice bath, and obtain liquid A. Dissolve 1 mol of dicyclohexylcarbodiimide (DCC) in 15 mL of dichloromethane, and drop the obtained liquid B into the above-mentioned liquid A in the ice bath within 15 min. After the dropwise addition is completed, react at 10°C ± 2°C for 24 h. After the reaction is completed, filter the reaction mixture, then wash with dichloromethane, tetrahydrofuran and petroleum ether in turn, and then place it in a nitrogen oven overnight to evacuate, and obtain acrylic acid surface-modified silver powder, which is recorded as A3.

[0035] Preparation Example 4

[0036] The acrylic acid surface-modified silver powder was prepared according to the method of Preparation Example 1, except that the acrylic acid was replaced by the same molar amount of methacrylic acid. The other conditions were the same as Preparation Example 1 to obtain acrylic acid surface-modified silver powder, which was recorded as A4.

[0037] Preparation Example 5

[0038] The acrylic acid surface-modified silver powder was prepared according to the method of Preparation Example 1, except that the acrylic acid was replaced by the same molar amount of 2-ethylacrylic acid. The other conditions were the same as Preparation Example 1 to obtain acrylic acid surface-modified silver powder, which was recorded as A5.

[0039] Comparative Example 1

[0040] Acrylic acid surface-modified silver powder was prepared according to the method of Preparation Example 1, except that acrylic acid was replaced by acetic acid in the same molar amount. The other conditions were the same as Preparation Example 1, and acetic acid surface-modified silver powder was obtained, which was recorded as DA1.

[0041] Example 1 Conductive adhesive and preparation method thereof

[0042] In parts by weight, 20 parts of isobornyl methacrylate, 4 parts of polyurethane acrylate oligomer, and 1 part of dicumyl peroxide were mixed evenly in a container to obtain a premix. 15 parts of the above-mentioned acrylic surface modified silver powder A1 and 55 parts of silver powder were added to the premix and mixed evenly, and then transferred to a double planetary hybrid stirring kettle and stirred for 20 minutes, and the wall was scraped when the stirring time was 15 minutes. After the stirring was completed, vacuum degassing treatment was performed, and the material was discharged to obtain a conductive adhesive.

[0043] Example 2 Conductive adhesive and preparation method thereof

[0044] In parts by weight, 18 parts of isobornyl methacrylate, 6 parts of polyurethane acrylate oligomer, and 0.5 parts of dicumyl peroxide were mixed evenly in a container to obtain a premix. 7.2 parts of the above-mentioned acrylic surface modified silver powder A1 and 40.8 parts of silver powder were added to the premix and mixed evenly, and then transferred to a double planetary hybrid stirring kettle and stirred for 20 minutes, and the wall was scraped when the stirring time was 15 minutes. After the stirring was completed, vacuum degassing treatment was performed, and the material was discharged to obtain a conductive adhesive.

[0045] Example 3 Conductive adhesive and preparation method thereof

[0046] In parts by weight, 22 parts of isobornyl methacrylate, 2 parts of polyurethane acrylate oligomer, and 1 part of dicumyl peroxide were mixed evenly in a container to obtain a premix. 24 parts of the above-mentioned acrylic surface modified silver powder A1 and 72 parts of silver powder were added to the premix and mixed evenly, and then transferred to a double planetary hybrid stirring kettle and stirred for 20 minutes, and the wall was scraped when the stirring time was 15 minutes. After the stirring was completed, vacuum degassing treatment was performed, and the material was discharged to obtain a conductive adhesive.

[0047] Example 4 Conductive adhesive and preparation method thereof

[0048] A conductive adhesive was prepared according to the method of Example 1, except that the acrylic surface modified silver powder A1 was replaced by the acrylic surface modified silver powder A2 of the same weight, and the other conditions were the same as in Example 1 to obtain a conductive adhesive.

[0049] Example 5 Conductive adhesive and preparation method thereof

[0050] A conductive adhesive was prepared according to the method of Example 1, except that the acrylic surface modified silver powder A1 was replaced by the acrylic surface modified silver powder A3 of the same weight, and the other conditions were the same as in Example 1 to obtain a conductive adhesive.

[0051] Example 6 Conductive adhesive and preparation method thereof

[0052] A conductive adhesive was prepared according to the method of Example 1, except that the acrylic surface modified silver powder A1 was replaced by the acrylic surface modified silver powder A4 in the same weight portion, and the other conditions were the same as in Example 1 to obtain a conductive adhesive.

[0053] Example 7 Conductive adhesive and preparation method thereof

[0054] A conductive adhesive was prepared according to the method of Example 1, except that the acrylic surface modified silver powder A1 was replaced by the acrylic surface modified silver powder A5 of the same weight portion, and the other conditions were the same as in Example 1 to obtain a conductive adhesive.

[0055] Example 8 Conductive adhesive and preparation method thereof

[0056] A conductive adhesive was prepared according to the method of Example 1, except that isobornyl methacrylate was replaced by methyl methacrylate in the same weight portion, and the other conditions were the same as those of Example 1 to obtain a conductive adhesive.

[0057] Comparative Example 1 Conductive adhesive and preparation method thereof

[0058] A conductive adhesive was prepared according to the method of Example 1, except that the acrylic acid surface-modified silver powder A1 was replaced by the acetic acid surface-modified silver powder DA1 in the same weight portion, and the other conditions were the same as in Example 1 to obtain a conductive adhesive.

[0059] Comparative Example 2 Conductive adhesive and preparation method thereof

[0060] A conductive adhesive was prepared according to the method of Example 1, except that the acrylic surface modified silver powder A1 was replaced by the same weight portion of unmodified silver powder, and the other conditions were the same as in Example 1 to obtain a conductive adhesive.

[0061] Comparative Example 3 Conductive adhesive and preparation method thereof

[0062] A conductive adhesive was prepared according to the method of Example 1, except that the amount of acrylic surface-modified silver powder A1 was 3.5 parts by weight and the amount of unmodified silver powder was 66.5 parts by weight, and the other conditions were the same as in Example 1 to obtain a conductive adhesive.

[0063] Comparative Example 4 Conductive adhesive and preparation method thereof

[0064] A conductive adhesive was prepared according to the method of Example 1, except that the amount of acrylic surface modified silver powder A1 was 875 parts by weight and the amount of unmodified silver powder was 175 parts by weight. At this time, the mass ratio of acrylic resin to silver powder was 100:1500, and the other conditions were the same as in Example 1 to obtain a conductive adhesive.

[0065] Test Case

[0066] The conductive adhesives obtained in the above examples and comparative examples were tested for performance according to the following method, and the results are shown in Table 1.

[0067] (1) Viscosity test: A Brookfield viscometer was used to test the viscosity of the conductive adhesive immediately after preparation and after standing for 24 hours. The test conditions included: measuring the viscosity at room temperature (25°C) with a 29# rotor rotating at 5 rpm for 30 minutes.

[0068] (2) Adhesion test: The conductive adhesive is coated on the silicon wafer, and then covered and pressed on the copper substrate, and then cured at 175℃ / 30min to obtain a test sample. The bonding area of ​​the test sample is 2mm×2mm, and the thickness of the adhesive layer is 50μm. The Dage 4000 is used to test the adhesion of the cured test sample: (i) room temperature adhesion test at 30℃; (ii) high temperature adhesion test at 260℃. Among them, the adhesion test method is: the sample to be tested is subjected to an adhesion test on a tensile testing machine with a heating box, one side of the sample is fixed, and a tensile force is applied to the other side. The tensile force is gradually increased until the silicon wafer is separated from the copper substrate. The tensile force value is recorded, and the ratio of the tensile force value to the bonding area is the adhesion force.

[0069] (3) Bubble test: The conductive adhesive is coated on the silicon wafer, and then covered and pressed on the copper substrate, and then cured at 175℃ / 30min to obtain a test sample. The bonding area of ​​the test sample is 2mm×2mm, and the thickness of the adhesive layer is 50μm. The test sample is placed under an X-ray instrument for detection and photography. The bubble situation is as follows Figure 2 shown.

[0070] Table 1

[0071]

[0072]

[0073] From Table 1 and Figure 2 It can be seen that the conductive adhesive obtained in the embodiment will not generate bubbles and lightning cracks after curing, and can obtain higher bonding strength at the metal interface, thus avoiding the problem of reliability failure of the conductive adhesive after curing. However, the conductive adhesive obtained in the comparative example will generate bubbles and lightning cracks after curing, and the bonding strength obtained at the metal interface is low, which is easy to cause reliability failure after curing.

[0074] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations on the present invention. A person skilled in the art may change, modify, replace and modify the above embodiments within the scope of the present invention without departing from the principles and intent of the present invention.

Claims

1. A conductive adhesive, characterized in that: The conductive adhesive contains acrylic resin, silver powder and an initiator, the silver powder contains at least 10wt% of acrylic surface-modified silver powder, and the mass ratio of the acrylic resin to the silver powder is 100:(100-1000).

2. The conductive adhesive according to claim 1, characterized in that: The silver powder contains 5-50 wt % of acrylic acid surface-modified silver powder and 50-95 wt % of unmodified silver powder.

3. The conductive adhesive according to claim 1, characterized in that: The acrylic acid surface modified silver powder is prepared according to the following method: S1. hydroxylating the surface of the silver powder to be modified to obtain hydroxylated silver powder; S2. The hydroxylated silver powder and the acrylic compound are subjected to a Steglich esterification reaction to obtain the acrylic surface-modified silver powder.

4. The conductive adhesive according to claim 3, characterized in that: In step S1, the step of hydroxylating the surface of the silver powder includes: placing the silver powder to be modified in a hydrogen peroxide solution at 40°C to 60°C for reaction for 10min to 60min, then washing the obtained reaction product with tetrahydrofuran and deionized water in sequence, and then drying the obtained washed product to obtain hydroxylated silver powder.

5. The conductive adhesive according to claim 3, characterized in that: In step S2, the usage ratio of the acrylic compound to the hydroxylated silver powder is (0.5-2) mol:1 g.

6. The conductive adhesive according to claim 3, characterized in that: In step S2, the Steglich esterification reaction is carried out in the presence of dimethylaminopyridine and dicyclohexylcarbodiimide; the conditions of the Steglich esterification reaction include a temperature of 0° C. to 30° C. and a time of 10 h to 48 h.

7. The conductive adhesive according to claim 3, characterized in that: In step S2, the acrylic compound is selected from at least one of acrylic acid, methacrylic acid and 2-ethylacrylic acid.

8. The conductive adhesive according to any one of claims 1 to 7, characterized in that: The acrylic resin contains acrylate monomers and polyurethane acrylate oligomers; Preferably, based on the total weight of the acrylic resin, the proportion of the acrylate monomer in the acrylic resin is 75-95wt%, and the proportion of the polyurethane acrylate oligomer is 5-25wt%; Preferably, the acrylate monomer is selected from at least one of acrylic acid, methacrylic acid, methyl acrylate, methyl methacrylate, ethyl acrylate, ethyl methacrylate and isobornyl methacrylate.

9. The method for preparing the conductive adhesive according to any one of claims 1 to 8, characterized in that: The method comprises mixing acrylic resin, silver powder and an initiator uniformly.

10. Use of the conductive adhesive according to any one of claims 1 to 8 in the assembly of electronic products.